2019
DOI: 10.1155/2019/1940692
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Performance and Deicing Effect of Sustained‐Release Snow Melting Asphalt Mixture

Abstract: To accelerate snow and ice melting, traditional chloride-based salts are spreaded on asphalt pavement surface, causing serious environmental pollution and infrastructure corrosion. For sustained-release snow melting asphalt mixture, the snow melting agent of Mafilon is directly added to asphalt mixture by replacing partial mineral powder to develop a new type of functional asphalt mixture. In this paper, through the Marshall test, immersion Marshall test, rutting test, trabecular bending test, and Cantabro tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It has been proven that the addition of salt-storage additives reduces pavement performance, particularly in terms of water stability [ 12 , 13 , 14 , 15 ]. Furthermore, the long-term high-temperature performance, low-temperature performance, and water stability of self-ice-melting asphalt pavements deteriorate with the continuous precipitation of salt during soaking treatment [ 12 , 16 , 17 ]. Fortunately, the negative impact of salt-storage additives on the pavement performance of asphalt mixtures can be mitigated by adding 0.3% polyester fiber to mixtures [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proven that the addition of salt-storage additives reduces pavement performance, particularly in terms of water stability [ 12 , 13 , 14 , 15 ]. Furthermore, the long-term high-temperature performance, low-temperature performance, and water stability of self-ice-melting asphalt pavements deteriorate with the continuous precipitation of salt during soaking treatment [ 12 , 16 , 17 ]. Fortunately, the negative impact of salt-storage additives on the pavement performance of asphalt mixtures can be mitigated by adding 0.3% polyester fiber to mixtures [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the long-term high-temperature performance, low-temperature performance, and water stability of self-ice-melting asphalt pavements deteriorate with the continuous precipitation of salt during soaking treatment [ 12 , 16 , 17 ]. Fortunately, the negative impact of salt-storage additives on the pavement performance of asphalt mixtures can be mitigated by adding 0.3% polyester fiber to mixtures [ 14 , 16 ]. The deicing effect of self-ice-melting asphalt pavements depends mainly on the salt precipitation rate, which is mostly influenced by the amount of salt-storage additives [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the ζ electric potential test method, suitable polymer materials were selected for the interface film to wrap the snow-melting salt and form a microencapsulated structure [30]. After mixing with the emulsified asphalt, the two phases reached thermodynamic equilibrium and formed a stable emulsified asphalt-based snow-melting stock solution [31].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported that the anti-icing longevity of APSSA can be calculated with predictive equations incorporating laboratory experiments (Giuliani et al, 2012;Liu et al, 2014;Ma et al, 2016;Zheng et al, 2016Zheng et al, , 2015Zhong et al, 2018;Zhou et al, 2019). However, these estimations were overly simplified, rough, and inaccurate because of lack of a first-principles-based or mechanistic model.…”
Section: Introductionmentioning
confidence: 99%